2019
DOI: 10.1098/rsos.190196
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of high thermal stability and colourless polyimides containing pyridine

Abstract: A novel aromatic diamine containing pyridyl side group, 4-pyridine-4,4-bis(3,5-dimethyl-5-aminophenyl)methane (PyDPM), was successfully synthesized via electrophilic substitution reaction. The polyimides (PIs) containing pyridine were obtained via the microwave-assisted one-step polycondensation of the PyDPM with pyromellitic dianhydride (PMDA), 3,3′,4,4′-biphenyltetracarboxylic dianhydride (BPDA), 3,3′,4,4′-diphenylether tetracarboxylic dianhydride (ODPA) and 4,4′-(hexafluoroisopropylidene)diphthalic anhydrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…OHADA can be obtained by dehydration of OHATA with excess acetic anhydride. As OHADA is nearly insoluble in common solvent at room temperature, it has to be characterized by 13 C solid state NMR. As well known, CHDA has several a steric structures [33,34] so OHADA should also has complicated steric structure, which can be observed from its 13 C solid state Scheme 1.…”
Section: Monomer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…OHADA can be obtained by dehydration of OHATA with excess acetic anhydride. As OHADA is nearly insoluble in common solvent at room temperature, it has to be characterized by 13 C solid state NMR. As well known, CHDA has several a steric structures [33,34] so OHADA should also has complicated steric structure, which can be observed from its 13 C solid state Scheme 1.…”
Section: Monomer Synthesismentioning
confidence: 99%
“…Another effective way to transparent PIs is to use monomers containing nonconjugated spacer such as diphenylether diamine [12] or triphenylmethylene diamine. [13] One of the most promising approach is to synthesize semi-aromatic PIs consisting of aromatic diamines and alicyclic dianhydrides, such as 1,2,3,4butanetetracarboxylic dianhydride (BT), [14] 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), [15] 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride (DM-CBDA), [16] 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), [17] 1S,2R,4S,5Rcyclohexanetetracarboxylic dianhydride (CHDA), [4,18] bicyclo-[2.2.2]oct-7-ene-2-exo,3-exo,5-exo,6-exo-2,3 : 5,6-dianhydride (BTA), [19] bicyclo[2.2.2]octane-2,3,5,6-tetracarboxylic 2,3 : 5,6-dianhydrides (H-BTA), [20] 3,3',4,4'-bicyclohexyltetracarboxylic dianhydride (H-BPDA), [21] 5-(2,5-Dioxytetrahydrofuryl)-3-methyl-3cyclohexene-1,2-dicarboxylic anhydride (CDA), [22,23] cyclopentanone bis-spironorbornanetetra carboxylic dianhydride (CpODA) [24] and 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic dianhydride (TDA) [25] as show in Scheme 1. [4,18,26,27] Although these semi-aromatic PIs always have high optical transparency, good solubility and low CTE, they still suffer from the relatively low thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…The irradiation time is a key parameter that can easily turn from a benefit to a drawback. Too long irradiation times or too high irradiation powers are many times translated into PIs of lower molecular mass, due to the partial degradation of the polymer [118].…”
Section: Synthesis Of Pis In Microwave Conditionsmentioning
confidence: 99%
“…The one-stage polycondensation mechanism, combined with a small heating time and reduced (if any) contact with solvent usually translates in higher optical transparencies as compared to PI analogs obtained by the classical method [118].…”
Section: Synthesis Of Pis In Microwave Conditionsmentioning
confidence: 99%
“…The introduction of aromatic bulky side-chain substituents is generally adapted to improve the T g s, solubility, and the dielectric properties of polymers, without affecting their thermal stability and mechanical strength much. , 4,4′-Diaminotriphenylmethane (TPM) and its derivatives, with the pendant phenyl ring and the free internal rotated structure, have attracted great attention. Aguilar-Lugo et al reported two series of aromatic polyimides (PI) based on 4,4′-diaminodiphenylmethane (DPM) or TPM with three commercial dianhydrides . The TPM-based PI shows an improvement in solubility, thermal stability, density, and free volume in comparison with the DPM-based PI.…”
Section: Introductionmentioning
confidence: 99%